Catalytically Active Nickel–Nickel Bonds Using Redox-Active Ligands - Uyeda, Christopher; Steiman, Talia J.; Pal, Sudipta (Synlett, 2016)
Advances in catalytic methodology are limited by the available tools for systematically optimizing catalyst structure. For molecular transition-metal catalysts, this optimization process typically involves two principle parameters: the identity of the active metal center and the environment presented by supporting ligands. In this Account, we highlight our group’s efforts to exploit nuclearity as a parameter in catalyst design. We recently reported a binucleating naphthyridine–diimine (NDI) ligand that supports coordinatively unsaturated nickel–nickel bonds across a broad range of formal oxidation states. Taking advantage of ligand-centered redox activity, these dinickel complexes function as robust platforms for catalytic transformations, including hydrosilylation and alkyne cyclotrimerization reactions. Our results collectively demonstrate that nuclearity effects provide a complementary means of modulating the activity and selectivity of transition metal catalysts.1 Introduction2 Group 10 Metal–Metal Bonds in Catalysis3 Dinuclear Nickel Complexes Supported by Redox-Active Ligands4 Multielectron Redox Transformations at Metal–Metal Bonds5 Dinuclear Silane Activation and Catalytic Hydrosilylations6 Selective Alkyne Cyclotrimerization7 Conclusions
Keywords: catalysis; dinuclear transition-metal complexes; metal–metal bonds; hydrosilylation; cycloaddition